Caracterização e análise da ruptura do solo de fundação de uma residência - estudo de caso - Nunes, Jandira Carla Rodrigues (Universidade Federal Rural do Semi-Árido, 2019)
The study of the soil has been much requested in the last decades, before problems occurred in the past and are very common still today, as recharges, cracking, cracks, among several other problems. The success of civil construction depends, among other factors, on studies, with quality and efficiency, of the land where the work will be installed, in order to design structures of secure foundations. The soil of a foundation acts on the support and distribution of the stresses applied by a construction. Due to its fundamental role in maintaining the stability of a work, great focus should be given to the design stage. For this, a study is carried out that involves several steps, starting in the field, going to the laboratory and ending at the project office. This work was carried out using the following research methods: bibliographical, case study, field study, experimental, modeling and simulation. The mathematical modeling was implemented in Excel software and the simulations were carried out in the Shoe module of GEO5 software. The analyzed samples were collected at a specific point of the terrain, close to the analyzed shoes, through probing to the characterization and assembly of the geotechnical profile. It was estimated the total request voltage, due to the sum of the stresses due to each of the shoes, since the interaction between its bulbs was observed, and with this, the equivalent shoe that transmitted to the ground was implemented in Excel and GEO5 software total requesting voltage. The obtained result showed that the safety coefficient does not satisfy the standard requirement for superficial foundations, making possible the rupture of the foundations of the work and increasing even more the probability of the occurrence of pathological manifestations. In addition, soil behavior may be worsened due to the presence of fine grains present in the soil, which had a high activity index. It was suggested that the solution to the problems proposed in this work could be a mineralogical study of clays present, a more in-depth survey and the design and execution of structural reinforcement projects in the foundations.
Monografia
Keywords: Bulbos de tensão; GEO5; Tensão admissível; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA